"Apple Far from the Tree": comparative effectiveness of fiberoptic single-operator cholangiopancreatoscopy (FSOCP) and digital SOCP (DSOCP). Issue 3 (March 2018) - Mizrahi, Meir; Khoury, Tawfik; Wang, Yan; Cohen, Jonah; Sheridan, Jennifer; Chuttani, Ram; Berzin, Tyler M.; Sawhney, Mandeep S.; Pleskow, Douglas K.
Abstract: Background: While the fiberoptic single-operator cholangiopancreatoscopy (FSOCP) system has demonstrated efficacy in the diagnosis and management of pancreaticobiliary diseases, the digital SOCP (DSOCP) appears to provide higher resolution digital imaging, however a comparison of these devices has not been established. The aim of this work was to compare the efficacy of FSOCP and DSOCP in biliary stone disease and indeterminate biliary strictures. Methods: A retrospective analysis of a prospective cohort was performed in patients undergoing FSOCP or DSOCP demographics included indication, diagnostic yield, procedure time, radiation dose, and complications. Results: 324 patients underwent cholangioscopy. FSOCP and DSOCP were utilized in 198 and 126 patients respectively. Male/female ratio was similar and mean age was 66 ± 13 years. Indications included stone disease, indeterminate stricture evaluation and "other" were 47%, 42% and 11% respectively. Mean procedure time for stone disease and the amount of radiation doses in DSOCP group were lower than the FSOCP group ( P = 0.032 and P = 0.02, respectively). Diagnostic yield in indeterminate strictures was higher 78% with DSOCP system compared to 37% with FSOCP system ( P = 0.004). Complication were low and similar between the groups. Conclusions: DSOCP system provides enhanced diagnostic yield, shorter procedure times and less radiation exposure compared to FSOCP system.